Public’s perception on government’s public communication in handling covid-19 - Centurion Chandratama Priyatna; Marroli Jeni Indarto; FX Ari Agung Prastowo (Jurnal Kajian Komunikasi, 2021)
Covid Task Force was assigned to handle the spread of the covid-19 virus, which keeps increasing and has caused loss of life and materials in various sectors. The task force is required to act quickly and accurately and keep focused, integrated, and synergic with ministries and regional government institutions. In doing its duty, the task force made many efforts, including implementing medical approaches such as preparing reliable medical staff and hospital facilities, implementing legal approaches such as issuing regulations to limit people from gathering or doing activities that may attract many people, and implementing communicative approach by delivering persuasive messages to encourage people to participate in accelerating covid-19 alleviation efforts. Communication strategies are implemented through various media to disseminate persuasive messages. Communicators are also trained to be a source of information regarding handling covid-19. They have to disseminate information to the public concerning strategies that the government is implementing to support and trust the government’s efforts.  In addition, the government also has to compose persuasive communication to encourage people to follow regulations and recommendations to suppress the spread of covid-19.  The government’s public communication efforts can succeed when it involves all communication channels, both the conventional and the new media, such as online and social media. In a crisis, media should be used as a friendly platform; therefore, through the task force, the government should provide complete and comprehensive information in the media.